Effects of levosimendan on ventriculo-arterial coupling and cardiac efficiency in paediatric patients with single-ventricle physiology after surgical palliation: retrospective study. (27th January 2020) - Iacobelli, Roberta; Ricci, Zaccaria; Marinari, Eleonora; Haiberger, Roberta; Di Molfetta, Arianna; Toscano, Alessandra; Di Chiara, Luca
Abstract: : OBJECTIVES: The use of levosimendan for paediatric patients with low cardiac output after congenital heart surgery has been recently described. We sought to evaluate ventriculo-arterial coupling (VAC) and other ventricular energetic parameters before and after 72 h from levosimendan start in infants with single-ventricle physiology and cardiac failure after palliation with Norwood or hybrid procedures. METHODS: In this single-centre retrospective study, 9 consecutive patients affected by hypoplastic left heart syndrome-like anatomy were retrospectively analysed. Systolic elastance, diastolic elastance, arterial elastance, VAC and cardiac mechanical efficiency were calculated by measuring, through 2-dimensional echocardiography, end-systolic volume and end-diastolic volume and by recording mean arterial pressure and central venous pressure. RESULTS: The median (range) weight and age were 2.8 (2.3–6) kg and 16.5 (6–116) days, respectively. After 72 h from levosimendan start, end-systolic volume significantly decreased (−1 ml, −3.2 to −0.1, P = 0.007), whereas mean arterial pressure and end-diastolic volume remained stable. Heart rate showed a significant decrease (−28 beats/min, −41 to 22, P = 0.008). Systolic elastance (2.9 mmHg/ml, 0.4–5.4, P = 0.008), arterial elastance (−5.9, −24 to −0.5, P = 0.038), VAC (−0.86, −1.5 to −0.16, P = 0.009) and cardiac mechanical efficiency (0.18, 0.03–0.22, P = 0.008) differences also showed significant modifications. CONCLUSIONS: In a small case series of patients with single-ventricle physiology, levosimendan showed to improve contractility and optimize VAC, with a reduction of heart rate. Monitoring of VAC and ventricular energetics can be an interesting aspect to improve the management of heart failure in infants with univentricular anatomy.